Human herpes virus 8-positive germinotropic lymphoproliferative disorder: first case diagnosed in the UK, literature review and discussion of treatment options. Issue 9 (2nd September 2020) - Ghoneima, Ahmed; Cooke, Joanna; Shaw, Emily; Agrawal, Avi
Abstract : We present this case of human herpes virus 8-positive germinotropic lymphoproliferative disorder in a 20-year-old woman seen in the surgical oncology clinic for localised lymphadenopathy. This is the first case to be reported in the UK, and we discuss it along with a literature review including investigations and treatment options. This will demonstrate the importance of preoperative workup and multidisciplinary teamwork in deciding management plans and serve as a guide for future encounters of this rare condition in clinical practice.